METHODS OF Z-CLASSIFIERS LEARNING - D. A. Lavnikevich; M. M. Tatur (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The use of genetic and gradient algorithms for learning classifiers based on Z-model was considered. Combined method of consistent applying this algorithms was offered. The resulting method allows to calculate all model parameters including integer ones and provides acceptable model training quality.